Inovasi Bentuk Lamang Tungkek Sebagai Kue Khas Tradisional Minangkabau: Inovasi Bentuk Lamang Tungkek - Velina Irawan; Fridayati, Lucy; Gusnita, Wiwik; Holinesti, Rahmi (Pasundan Food Technology Journal (PFTJ), 2026)
This study aimed to evaluate the effect of form innovation of Lamang Tungkek on panelists’ preference levels using a hedonic test. The research involved one control sample and three innovative samples, which were evaluated by 24 panelists. The sensory attributes assessed included shape, color, texture, aroma, and taste. The data were analyzed descriptively based on the mean values of the hedonic test. The results showed that sample 234 consistently achieved the highest mean preference scores across most sensory attributes. Variations in hedonic test values indicated differences in panelists’ acceptance of the Lamang Tungkek form innovations. Form innovation primarily influenced panelists’ perception of texture, while the other sensory attributes remained generally well accepted. It can be concluded that the form innovation of Lamang Tungkek has the potential to enhance panelists’ acceptance without diminishing the product’s sensory characteristics. Sample 234 shows strong potential for further development as a traditional food product that is adaptive to modern consumer preferences.Keywords: Lamang Tungkek, Form Innovation, Hedonic Test, Sensory Evaluation.